2008
DOI: 10.5694/j.1326-5377.2008.tb02221.x
|View full text |Cite
|
Sign up to set email alerts
|

World Youth Day 2008: did it stress Sydney hospitals?

Abstract: Objective: To characterise the nature and impact of World Youth Day (WYD) 2008 on emergency department (ED) presentations at key hospitals. Design, setting and participants: Retrospective analysis of WYD pilgrims presenting to the EDs of St Vincent's Hospital and Sydney Hospital, 9–23 July 2008. Main outcome measures: Frequency of pilgrim ED presentations; presenting complaint, Australasian Triage Scale category, diagnosis, admission to hospital and demographic characteristics. Results: 191 pilgrims presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Olympic Games and World Cup football tournament) or recurrent events at the same location (e.g. the Hajj pilgrimage in Saudi Arabia) [6].…”
mentioning
confidence: 99%
“…Olympic Games and World Cup football tournament) or recurrent events at the same location (e.g. the Hajj pilgrimage in Saudi Arabia) [6].…”
mentioning
confidence: 99%
“…Variation existed in the studies regarding the impact of MGEs on local hospitals. Eight studies reported a raw number of patients who presented or were admitted to EDs/hospitals, (ranging from three to 401), 19,20 while the other three studies reported either the rate of patient presentations to EDs (0.005/1000) 21 or hospital administration rate (3.6-102/1000). 22,23 Syndromic Indicators used in EDs for Communicable Diseases Most studies (n = 7; 64%) mentioned the use of a surveillance system based on patients' signs and symptoms.…”
Section: Measurement Of Ed Activities During Mgesmentioning
confidence: 99%
“…33 Previous studies have reported some syndromes used to detect communicable diseases during MGEs, such as fever, rash, and abdominal pain, indicating diseases such as measles, influenza, and respiratory tract infections. [23][24][25] However, information as to the exact SIs and corresponding diagnosis codes (ie, International Classification of Diseases 10th Revision [ICD-10]) used to detect the impact of communicable diseases on EDs in MGE is still very limited, 21,30 which makes comparative research and recommendations for standardized Figure 1. PRISMA Flow Diagram, Adapted from Liberati, et al 15 Abbreviations: ED, emergency department; MGE, mass-gathering event; PRISMA, Preferred Reporting Items for Systematic Reviews and Meta-Analyses.…”
Section: Syndromic Indicators Used In Eds For Communicable Diseasesmentioning
confidence: 99%
“…Mass gatherings are one of the most significant items on the global health security agenda [3] and can occur spontaneously without previous alerts, such as political rallies, protests, or planned gatherings. They can be either periodic at different localities like the Olympics and World Soccer Cup or repeated events at the same place like the Hajj in Saudi Arabia, which is one of the largest mass gathering worldwide [4].…”
Section: Introductionmentioning
confidence: 99%